Protection of WEB-sources of attacks like COMMAND EXECUTION - Пархоменко, Іван Іванович; Воскобойніков, Андрій Олегович (Ukrainian Information Security Research Journal, 2012)
Currently, the Internet increases the number of web pages. Many of them retain confidential information about users, so it is important to ensure its protection. The objective is to find and offer protection against the most common attacks - XSS and SQL injection. Since the main reason for these vulnerabilities is the lack of filtration, protection must be built on it. In this work, the mechanism of filtering incoming data based on regular expressions is proposed.